2023
DOI: 10.1149/2162-8777/acc7c7
|View full text |Cite
|
Sign up to set email alerts
|

Visible–Near Infrared Scintillation Properties of Er-Doped Bi4Si3O12 Single Crystals

Abstract: We synthesized the 0.5, 1.0, 2.0, and 3.0% Er-doped Bi4Si3O12 (BSO) single crystals and researched the photoluminescence (PL) and scintillation properties in visible–near infrared ranges. The X-ray diffraction analysis indicated that the synthesized samples had single-phase structure of BSO. In transmission spectra, all the samples had some absorption peaks owing to the 4f-4f transitions of Er3+ ions. In PL and scintillation properties, all the samples had the emission peaks due to the 6p-6s transition of Bi3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The excitation wavelength of the intrinsic luminescence of Mg4Ta2O9 is 220 nm [32], which is outside the measurable range of the instrument used in this study, so no emission was observed in Figure 3a. In Figure 3b, an emission peak at 1550 nm under excitation light at 380 nm and 520 nm was observed, which was attributed to the 4f−4f transitions of Er 3+ [43,44]. The spectral characteristics of the other samples were consistent with that of the Mg4Ta2O9 doped with 0.1% Er.…”
Section: Pl Propertiessupporting
confidence: 62%
See 1 more Smart Citation
“…The excitation wavelength of the intrinsic luminescence of Mg4Ta2O9 is 220 nm [32], which is outside the measurable range of the instrument used in this study, so no emission was observed in Figure 3a. In Figure 3b, an emission peak at 1550 nm under excitation light at 380 nm and 520 nm was observed, which was attributed to the 4f−4f transitions of Er 3+ [43,44]. The spectral characteristics of the other samples were consistent with that of the Mg4Ta2O9 doped with 0.1% Er.…”
Section: Pl Propertiessupporting
confidence: 62%
“…For comparison, the Z eff , density, dose-response characteristics, and photodetector are summarized in Table 1. The dose rate response functions of Erdoped BGO and Bi 4 Si 3 O 12 (BSO) NIR scintillators evaluated in the same measurement system have been reported to show a lower detection limit of 0.006 Gy/h [44,49]. Previous studies reported a lower detection limit of 0.8 Gy/h in measurement systems combining commercially available Pr-doped Gd 2 O 2 S and Si-based photodetectors, 0.3 Gy/h for a system combining a Pr-doped BaTi 4 O 9 and an InGaAs-based photodetector, and 0.06 Gy/h for a Nd-doped SrY 2 O 4 and InGaAs-based system.…”
Section: Scintillation Propertiesmentioning
confidence: 95%